THE FACE OF ISLAMIC CIVILIZATION IN INDONESIA - Efferi, Adri (LPPM IAIN Kudus, 2017)
Islam is a source of civilization for its adherents, in accordance with the conception of the word civilization itself, which means the product of human life activity, whether in the field of politics, economy, social, education and so forth. So Islam as a religion, in its scriptures also gives clues about the things that are needed in human life, although it is not in the language of detailly. Enforcing the application of Arabic Islamic Shari'a into the society such as Indonesia, of course it will create feelings of alienation in religion. As an example is in the case of hijab for muslim woman (muslimah). Arabic or Middle Eastern dress models and veils are dark colors. If these models are used in Indonesian Moslem society, the wearer will look different and become strange in that society. Therefore it is needed to take a wise attitude in implementation the teaching of religion, so that it will be suitable with local culture that is already exists.